The challenges for training in the modality of teaching young people and adults: In evidence the perception of teachers in Belo Horizonte - da Silva , Leila Vaz (Seven Editora, 2024)
This research aimed to identify the challenges for the completion of the formative process of students enrolled in the Education Program for young people and adults, considering the perception of teachers in schools in Belo Horizonte. For the theoretical foundation of the study, the processes that seek to legitimize the core and evolution of Youth and Adult Education (EJA) in Brazil were exposed, as well as to present the historical trajectory of this teaching modality, with reference to the works of Haddad (2,000); DI Pierro; Joia, Ribeiro, (2,001); the legal frameworks made available by the MEC (2003); in addition to the characterization of the profile of these students based on data from the Basic Education Census (2,020). The methodological strategy adopted as to nature, applied research with a quantitative approach, being classified as descriptive, with a case study technique. The results indicate that EJA students are workers who study and that the main challenges to conclude the training process consist of reconciling work and study; tiredness; adaptation to the heterogeneity of the classes; the structure of the rooms; and focus arising from other concerns. The study may contribute to the development of educational policy strategies focused on reducing dropout in this modality of education. DOI:https://doi.org/10.56238/sevened2024.015-001